Development of a Schaum's Outline Series Module on Spin Angular Momentum for Physics Education Students: Feasibility Study and User Acceptance - Oktova, Raden; Putri, Risky Afandi; Sukarelawan, Moh. Irma; Hidayah, Rihmah Alifah (Universitas Ahmad Dahlan, 2026)
Spin angular momentum is an abstract concept in quantum mechanics that often causes conceptual and mathematical difficulties for Physics Education students. The limited availability of specific teaching materials tailored to the characteristics of prospective teachers has prompted the need to develop structured and contextual modules. This study aims to develop a quantum mechanics module on spin angular momentum that is suitable and appropriate for undergraduate Physics Education students. This study uses the Research and Development (R&D) method with the ADDIE model limited to the Development stage. The research subjects consisted of two Physics Education lecturers as validators and eleven students who had taken the Quantum Mechanics course. The instruments were expert validation questionnaires and student acceptance questionnaires using a 4-point Likert scale, while the data were analyzed descriptively and quantitatively in the form of percentages. The expert validation results showed a very feasible category in terms of material (94.4%), usefulness (87.5%), presentation (85.7%), and language (75%), as well as a feasible category in terms of graphics (71.8%). The student acceptance test showed a very satisfied category in all aspects, with percentages ranging from 89.20% to 94.31%. Thus, the developed module was declared feasible and very well accepted as self-learning material, and has the potential to support the strengthening of students' conceptual understanding.